2015
DOI: 10.4238/2015.june.18.19
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between promoter methylation in the GSTP1 gene and hepatocellular carcinoma development: a meta-analysis

et al.

Abstract: ABSTRACT. Epigenetic silencing of the GSTP1 gene by promoter methylation has been associated with increased risk and shortened survival in patients with hepatocellular carcinoma (HCC). We therefore conducted a meta-analysis to obtain a more precise estimate of this association. By searching the Cochrane Library, CBM, EMBASE, PubMed, and the Web of Science, we tabulated and analyzed parameters from each study. Results were summarized by meta-analyses using the version 12.0 STATA software. Odds ratios (ORs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Cell apoptosis was determined by fluorescence-activated cell sorting (FACS) analysis as described [37]. …”
Section: Methodsmentioning
confidence: 99%
“…Cell apoptosis was determined by fluorescence-activated cell sorting (FACS) analysis as described [37]. …”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that promoter hypermethylation is an epigenetic mechanism able to repress gene transcription by inhibiting the binding of transcription factors to their consensus sequences when methylated (Herman & Baylin, ). In the studies cited above, downregulation of GSTP1 gene expression was associated to an aberrant methylation in the promoter region (Chan et al., ; Li et al., ; Lin et al., ; Martignano et al., ; Mian et al., ; Shilpa et al., ; Zelic et al., ; Zhang et al., ). Moreover, promoter methylation of GSTP1 gene was detected in some body fluids of patients with prostate cancer and was proposed as a biomarker candidate for noninvasive detection of prostate cancer (Cairns et al., ; Goessl et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it was reported that loss of GSTP1 expression enhances cell susceptibility to acquire additional alterations and undergo further genetic changes toward tumor progression (Schnekenburger, Karius, & Diederich, 2014). In this field, several research works found lower GSTP1 expression in prostate cancer (Lin et al, 2001;Martignano et al, 2016;Mian et al, 2016;Zelic et al, 2016;Zhang et al, 2015), endometrial cancer (Chan et al, 2005), hepatocellular cancer (Li, Li, Gao, & Shi, 2015), and ovarian cancer (Shilpa, Bhagat, Premalata, Pallavi, & Krishnamoorthy, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…GSTP1 methylation is frequently associated with tumor development or poor prognosis in a wide range of tumors such as neuroblastoma [6], hepatocellular carcinoma [7], endometrial [8], breast [9], and prostate cancers (PCa) [10]. It is involved in the early process of carcinogenesis in PCa [11, 12] and its methylation has been largely investigated: about 70–80% of PCa cases are methylated, while benign prostatic hyperplasias are normally hypomethylated [13, 14].…”
Section: Introductionmentioning
confidence: 99%